Deliverable 1.4 Collaboration establishment - Sandven, Stein; Sagen, Hanne; Danielsen, Finn; Pirazzini, Roberta; Ahlstrøm, Andreas Peter; Voss, Peter; Cittorio, A.; Beszczynska-Möller, Agnieszka; Hamre, Torill; Gao, Yongqi (Zenodo, 2019)
One of the specific objectives of INTAROS WP1 is to establish collaboration with research groups and other actors who play an important role to develop multidisciplinary observing systems for the Arctic. This report described the activities and results of the connections and collaboration during the first 2.5 years of the project. In this period INTAROS has been present and given presentations at ≈ 150 meetings, workshops and conferences in order to establish collaboration with other projects, organisations and stakeholder groups involved in Arctic observing systems. The development of collaboration is a continuous ongoing process, in particular collaboration with EU Polarnet and the other H2020 projects under the Arctic Cluster is in progress. Also, collaboration with other projects and programmes in Europe, North America and Asia is under development. This includes SAON, Arctic Science Summit Week, Arctic Observing Summit, European projects, and projects in USA, Canada, Russia, China, Japan and South Korea. Such collaboration is required in order to build an integrated Arctic Observing System covering the pan-Arctic region. The collaboration includes participation in and organization of conference sessions, workshops, and stakeholder events across the pan-Arctic area. Furthermore, joint projects are established to fund more collaboration activities, including joint field experiments and data sharing agreements. Also MoUs are developed between institutions to enable long-term collaboration. In Europe, collaboration with Copernicus programme and various research infrastructure programmes is in progress, because these programmes have long-term funding perspectives and build on research priorities which incorporate Arctic observing. Through Copernicus services and Polar programmes under the Space Agencies, the production and delivery of satellite data for Arctic observing is growing strongly. The INTAROS consortium is well-connected to these programmes and exploits satellite data in a number of Arctic observing ...